At a meeting of delegates of the towns in the counties of New-London and Windham : convened at Norwich, the 8th day of September 1774, to consult for their common safety, &c. Hon. Gurdon Saltonstall, chairman. Col. William Williams, clerk - Williams, William, 1731-1811 (Printed by Judah P. Spooner, in Norwich., 1774)
Recommendations concerning supplying arms and preparing troop and military companies, following a meeting of delegates from New London and Windham Counties, which met in Norwich.